Implementation of Evidence‐Based Employment Services in Specialty Mental Health. (21st October 2013) - Hamilton, Alison B.; Cohen, Amy N.; Glover, Dawn L.; Whelan, Fiona; Chemerinski, Eran; McNagny, Kirk P.; Mullins, Deborah; Reist, Christopher; Schubert, Max; Young, Alexander S.
Abstract : Objective: Study a quality improvement approach for implementing evidence‐based employment services at specialty mental health clinics. Data Sources/Study Setting: Semistructured interviews with clinicians and administrators before, during, and after implementation. Qualitative field notes, structured baseline and follow‐up interviews with patients, semistructured interviews with patients after implementation, and administrative data. Study Design: Site‐level controlled trial at four implementation and four control sites. Hybrid implementation–effectiveness study with mixed methods intervention evaluation design. Data Collection/Extraction Methods: Site visits, in‐person and telephone interviews, patient surveys, patient self‐assessment. A total of 801 patients completed baseline surveys and 53 clinicians and other clinical key stakeholders completed longitudinal qualitative interviews. Principal Findings: At baseline, sites varied in the availability, utilization, and quality of supported employment. Each site needed quality improvement for this service, though for differing reasons, with some needing development of the service itself and others needing increased service capacity. Improvements in knowledge, attitudes, beliefs, and referral behaviors were evident in mid‐ and postimplementation interviews, though some barriers persisted. Half of patients expressed an interest in working at baseline. Patients at implementation sites were 2.3 times more likely to receive employment services during the study year. Those who had a service visit were more likely to be employed at follow‐up than those who did not. Conclusions: Studies of implementation and effectiveness require mixed methods to both enhance implementation in real time and provide context for interpretation of complex results. In this study, a quality improvement approach resulted in superior patient‐level outcomes and improved clinician knowledge, attitudes, and behaviors, in the context of substantial variation among sites.